2005
DOI: 10.1357/002224005774464238
|View full text |Cite
|
Sign up to set email alerts
|

Two coastal upwelling domains in the northern California Current system

Abstract: A pair of hydrographic sections, one north and one south of Cape Blanco at 42.9N, was sampled in five summers (1998 -2000 and 2002-2003). The NH line at 44.6N lies about 130 km south of the Columbia River, and spans a relatively wide shelf off Newport, Oregon. The CR line at 41.9N off Crescent City, California, lies 300 km farther south and spans a narrower shelf. Summer winds are predominantly southward in both locations but the southward winds are stronger on the CR line. Sampling included CTD/rosette casts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 46 publications
9
60
0
Order By: Relevance
“…Note that the Fe index is generally low where chlorophyll is elevated, a result of biological drawdown (and subsequent blooming of phytoplankton) of the iron injected into the surface mixed layer. Bay (Brzezinski et al, 1997;Kudela et al, 1997), the WEST region , the COAST region (Huyer et al, 2005), and the RISE region (Bruland et al, 2008;Kudela and Peterson, in et al (1997) concluded that silicic acid is unlikely to limit productivity, there was we now know that it is augmented by other sources. In particular, it has been suggested that upwelling due to Ekman divergence near the coastal boundary can be extended further offshore due to curl in the wind stress (Enriquez and Friehe, 1995;Munchow, 2000;Oke et al, 2002).…”
Section: The Role Of Nutrientsmentioning
confidence: 99%
“…Note that the Fe index is generally low where chlorophyll is elevated, a result of biological drawdown (and subsequent blooming of phytoplankton) of the iron injected into the surface mixed layer. Bay (Brzezinski et al, 1997;Kudela et al, 1997), the WEST region , the COAST region (Huyer et al, 2005), and the RISE region (Bruland et al, 2008;Kudela and Peterson, in et al (1997) concluded that silicic acid is unlikely to limit productivity, there was we now know that it is augmented by other sources. In particular, it has been suggested that upwelling due to Ekman divergence near the coastal boundary can be extended further offshore due to curl in the wind stress (Enriquez and Friehe, 1995;Munchow, 2000;Oke et al, 2002).…”
Section: The Role Of Nutrientsmentioning
confidence: 99%
“…However it is difficult to observe, given the small size of marine larvae, their large numbers, and their high mortality rates (Cowen & Sponaugle 2009), particularly in regions characterized by dynamic oceanography like the productive eastern boundary current systems. In these regions, wind interacts with nearshore bathymetry and shoreline topography to produce currents that are variable in both space and time (Largier et al 1993, Carr & Kearns 2003, Huyer et al 2005, Checkley & Barth 2009, García-Reyes & Largier 2010.…”
Section: Introductionmentioning
confidence: 99%
“…By use of the temperature-dependent hatching time observed for E. pacifica at 1uC and .20uC by Iguchi and Ikeda (1994) and our own measurements (7uC, 10uC, and 15uC), we find that development time can be estimated by HT 5 7.94 3 e 20.1244(T) (r 5 0.974, p , 0.001), where HT is hatching time expressed in days, and T is laboratory temperature of embryonic development (uC). The average summer vertical-temperature structure at the same location (NH-line: 44.6uN) where females were collected during the 1998-2003 sampling period have surface temperatures of 10uC near the coast, which warm up to 17uC offshore (160 km offshore) (Huyer et al 2005). The maximum vertical-temperature gradient is typically 10uC (17uC at surface to 7uC at 150-m depth).…”
Section: Discussionmentioning
confidence: 99%